1991
DOI: 10.1016/0014-5793(91)80849-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of upstream regulatory regions required for the activities of two promoters of the rat aldolase A gene

Abstract: Rat aldolase A gene has 2 promoters with different tissue specificities (M-and AH promoters). The M promoter is active only in adult skeletal muscle and induced during myogenesis, whereas the AH promoter is active ubiquitously in many tissues, including various cancer cells. Regulatory sequences for these promoters were investigated through assays for transient expression after introduction into myogenic and nonmyogenic cells. When M promoter-CAT fusion genes were transfected into primary cultures of chicken m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…MEF-2 plays an essential role in muscle-specific induction of the rat aldolase A gene. Recent studies have indicated that the region of the M promoter from -202 to -85 exhibits the properties of a muscle-specific enhancer in chicken primary myotubes differentiated in vitro (14). This region contains a single A/T-rich sequence, CTAAATATAG, which closely matches (9 of 10) the MEF-2 consensus sequence (41).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…MEF-2 plays an essential role in muscle-specific induction of the rat aldolase A gene. Recent studies have indicated that the region of the M promoter from -202 to -85 exhibits the properties of a muscle-specific enhancer in chicken primary myotubes differentiated in vitro (14). This region contains a single A/T-rich sequence, CTAAATATAG, which closely matches (9 of 10) the MEF-2 consensus sequence (41).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid constructions. The construction of pM202CAT and pM85CAT was described previously (14). The M promoter sequence in pM202CAT extends from 202 bp up- FIG.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations